2017
DOI: 10.3389/fnmol.2017.00285
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Declines Apoptosis, Ameliorates Mitochondrial Function and Improves Retinal Ganglion Cell Survival and Function in In Vivo Model of Glaucoma in Rat and Retinal Ganglion Cell Culture In Vitro

Abstract: Glaucoma is a progressive neuropathy characterized by the loss of retinal ganglion cells (RGCs). Strategies that delay or halt RGC loss have been recognized as potentially beneficial for rescuing vision in glaucoma patients. Quercetin (Qcn) is a natural and important dietary flavonoid compound, widely distributed in fruits and vegetables. Mounting evidence suggests that Qcn has numerous neuroprotective effects. However, whether Qcn exerts neuroprotective effects on RGC in glaucoma is poorly understood. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 55 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Four days before the first laser treatment, 2 μl of 5% of FluoroGold (FluoroGold; Sigma-Aldrich, St. Louis, MO, United States) was microinjected into the superior colliculus on each side of anesthetized rats, as described previously ( Gao et al, 2017 ). Eyes obtained from the rats 2 weeks after IOP elevation were fixed in 4% paraformaldehyde in PBS and prepared as flat-mount.…”
Section: Methodsmentioning
confidence: 99%
“…Four days before the first laser treatment, 2 μl of 5% of FluoroGold (FluoroGold; Sigma-Aldrich, St. Louis, MO, United States) was microinjected into the superior colliculus on each side of anesthetized rats, as described previously ( Gao et al, 2017 ). Eyes obtained from the rats 2 weeks after IOP elevation were fixed in 4% paraformaldehyde in PBS and prepared as flat-mount.…”
Section: Methodsmentioning
confidence: 99%
“…In the retina, we found that Qcn protected ARPE-19 cells from oxidative stress injury [14]. Other studies reported that Qcn has protective effects in the retina ischemia-reperfusion injury [15], ocular inflammation [16], and neuroprotective effects on RGC in glaucoma [17]. However, whether Qcn protects the RGCs in rAION is poorly understood.…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, Qcn preserved the visual function, prevented apoptosis of RGC, decreased the macrophage/microglial infiltration in the ONs, and impeded the secondary RGC death. Qcn was administered by intraperitoneal, oral, or intravitreal injection on the retina as described previously [17,22,23]. However, based on the pharmacodynamic maintenance and prolonged exposure of Qcn on the retina, we selected the intravitreal injection as the mode of Qcn administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be used as a protective agent against coronary diseases [ 38 ]. It has been shown that quercetin is a promising therapeutic agent for improving retinal ganglion cells (RGC) survival and function in glaucomatous neurodegeneration [ 39 ]. Low concentration of quercetin antagonizes glioblastoma cell invasion and angiogenesis in vitro [ 40 ].…”
Section: Discussionmentioning
confidence: 99%